Investigation of Earning Differentials Between Visible Minorities and Whites and Ethnic Groups: From Canadian Evidence - Lin, Hao (Université d'Ottawa | University of Ottawa, 2015)
This study carries out a sequential analysis of the earnings differentials between visible minorities and whites, as well as ethnic origins which are interacted with immigrant status for both men and women by using the data of the 2011 National Household Survey (NHS). The results show that immigrants earn less than Canadian-born workers for both genders, the earnings gap is larger for men than it is the case for women. Female immigrant visible minorities earn less than female immigrant whites, and all male visible minorities earn less compared with their white counterparts for both immigrants and non-immigrants. These differences can be mainly explained by the variables of the years since migration and the occupations of immigrants, and the educational attainments, the potential labour market experience of Canadian-born workers. Overall, almost all non-European origins earn substantially less than those immigrants of European origin and native-born workers after controlling for the effect of education, potential labour market experience, marital status, etc.